Suicide in old Norse and Finnish folk stories - Saxby Pridmore; J Ahmadi; ZA Majeed (2011)
Objective: The aim of this study was to examine the folk stories of Norway, Iceland and Finland with a view to discovering accounts of suicide as an escape option from intolerable predicaments, and to compare any such accounts with material from Southern Europe. Method: The Poetic Edda (Norway/Iceland) and The Kalevala (Finland) were examined for accounts of suicide, and evidence regarding the infl uence of these texts and individual accounts was collected. Results: The Poetic Edda provided one account and The Kalevala three accounts of suicide performed as a means of escaping intolerable situations. Both the Poetic Edda and The Kalevala are in public awareness and have infl uenced the politics and culture of their respective regions. The individual suicides have been depicted in literature, music and the visual arts, from the distant past to the present time. Conclusion: Suicide as a means of escape from intolerable predicaments has been public knowledge in these regions for a millennium. This is consistent with fi ndings from Southern Europe and substantiates that intolerable predicaments may lead to suicide.